Design of Hollow Nanofibrous Structures using Electrospinning: An Aspect of Chemical Sensor Applications. Issue 7 (25th May 2020) - Cho, Hee‐Jin; Kim, Yoon Hwa; Park, Seyeon; Kim, Il‐Doo
Abstract: Chemical gas sensors have attracted much attention with the purposes of environmental hazardous gas detection and health monitoring via exhaled breath analysis. In particular, semiconducting metal oxide (SMO)‐based chemiresistors have been considered as one of the most attractive sensing platforms owing to its simple operation, low cost, ease of miniaturization and integration to mobile devices. However, SMO‐based sensors suffer from sluggish gas reactions and poor responses. To enhance their sensing characteristics, one‐dimensional (1D) nanostructures with large surface area and high porosity are desired, since sensing reactions with analytes mainly occur at the surface of the sensing layers. In addition, uniform catalyst functionalization on SMO supports is beneficial in terms of gas response, reaction speed, and selectivity. In this review, we comprehensively highlight recent progresses on diverse hollow 1D nanofibrous structures prepared using a well‐reputed technique of electrospinning, and their unique morphological advantages as highly sensitive chemical sensing layers. Finally, future perspectives on the synthesis and sensing characterizations of hollow nanofibrous sensing materials functionalized with robust catalysts are discussed. Abstract : Semiconducting metal oxides‐based chemical sensors have attracted much attention for environmental hazardous gas detection and health monitoring. To further enhance the sensing characteristics, the rational design of metal oxides morphologies with large surface area and high porosity is an essential approach. We especially focus on diverse hollow 1D nanofibrous structures, prepared by electrospinning technique, and their applications on highly sensitive chemical sensing layers. In addition, future perspectives for metal oxides‐based chemical sensors are discussed.